Ideas de los alumnos acerca del mol. Estudio curricular - García Martín, J. P.; Pizarro Galán, A. Mª; Perera Cendal, F.; Martín Díaz, M. J.; Bacas Leal, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper a display is made of the controversy about the concept of mol and the convenience of introducing it in the school "curricula" at the age in which nowadays is made. The results we have obtained from the research carried out on the difficulties experienced by 15 to 19 year old students in understanding this concept and other related concepts are given.